(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Transition to a market economy in Iraq after 2003 Many of the negatives that have a direct impact on the economic sectors, Domestic markets have seen the entry of various types of foreign goods Beneficiaries of weak customs regulations and laws governing the entry of such goods Which directly affected the overall economic activity These conditions affect not only the productive sectors but also the realities of the consumer which has been greatly affected by the status quo, and has caused a lot of risks and damage Which resulted from the use or consumption of fraudulent or poor goods In addition to pollution of the environment by various types of pollutants,of the competent government agencies in dealing with these problems For the purpose of familiarity with global experiences in consumer protection, the experience of the United Kingdom has been addressed By addressing the most important administrative and legal procedures Through which the British Government has worked to provide the necessary protection to the consumer In the form that made the Kingdom of the leading and distinguished countries in this field In addition to the possibility of benefiting from this experience in Iraq.